Twilight on the range : recollections of a latterday cowboy. - Timmons, William, 1878-1965 (M.K. Brown range life series ;, 1962)
Though some scoundrels and cheaters are here, the narrative emphasizes--for a change--the good men of the West, men whose lives had wide influence over the lives of others. It speaks of an era when a man's word was more binding than a written contract and when personal integrity and industry were held in higher esteem than shrewdness. Mr. Timmons' characters bear no taint of the western types that many movie-goers and TV addicts have come to believe in. His men are real, the incidents undoctored. In this book you experience the terror of being lost in the dead-white expanse of a North Dakota snowstorm; the gaiety of cowboy dances, for which there were never enough women available; the excitement of a near-riot in a Hebron, North Dakota, saloon where cowboys from the 75 Ranch drank up or poured out all the liquor, then smashed all the glasses and bottles--one day before the state became bone-dry; and all the loneliness of work on a range, where a flickering lantern on the side of the chuck wagon on a stormy night meant home for many a cowboy. Running like a bright thread through the narrative is Billie Timmons' love of horses, from whom he learned the wisdom that some horses and some men are to be handled with great care and others are not to be handled at all. His chapter on Buck, his best-loved horse, is memorable -- Book jacket.